Analisis Stabilitas Lereng dengan Metode Bored Pile untuk Penanganan Tanah Longsor pada Ruas Jalan Muara Teweh – Jalan Pasar Punjung Sta 29+400 - Stephanus Alexsander; Fatma Sarie; Mohammad Ikhwan Yani; Nomeritae; Edsel Kennardo (Jurnal Serambi Engineering, 2025)
This study analyzed the slope stability of Muara Teweh road section - Jalan Pasar Punjung STA 29+400. A landslide occurred on the left side of the road with a height of 15 m and a length of 50 m. The analysis was performed using the finite element method with Plaxis 2d program to obtain a safety factor (SF) value based on secondary data from field and laboratory tests, after which the bored pile was designed and then reanalyzed to obtain the SF value. The initial SF of 1.847 was not consistent with field conditions (SF < 1.07), so a back-analysis was performed, resulting in an SF of 1.044. To prove that the analysis was correct, a comparison with Bishop's Limit Equilibrium Method was performed, yielding an SF = 1.000, so the value is correct. The design of the bored pile is planned with two vertical piles per point, each with a diameter of 0.5 m, length of 5 m, and spacing of 1 m along 50 m. For the size and number of reinforcements, 4D16 longitudinal bars and Ø10 - 100 mm stirrups were used. After stabilization, the SF increased to 1.260, meeting the minimum SF > 1.25, which indicates it is considered safe.